PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS DENGAN METODE SUGGESTOPEDIA PADA MAHASISWA SEMESTER II-E TBI STAIN PAMEKASAN - Sumihatul Ummah; Eko Ariwidodo; Afifah Raihany (OKARA: Jurnal Bahasa dan Sastra, 2015)
There are two problems in the result of research that will be discussed in this article. They are (1) how are the steps of the implementation of suggestopedia method in learning speaking English at the second semester students of E class TBI STAIN Pamekasan and (2) How are the increasing of speaking English skill for the second semester students of E class TBI STAIN Pamekasan in learning speaking English by using the suggestopedia method. The research method is classroom action research by using research strategy of Kemmis and Mc Taggert Model which consist of four (4) steps, namely planning, acting, observing, and reflecting. The result of research provided that classically for the 1st, 2nd, and 3rd cycle indicated the increasing of students learning completeness scores, each of them are 38.23%, 67.54%, and 82.35%. While the students performance for each aspects are increasing from the 1st cycle up to 3rd cycle. The students performance of speaking English activities in the classroom from each aspects that more appear was grammar with score 85.2%. for the 2nd cycle was comprehensibility with score 88.2% and vocabulary with score 88.2%, and for the 3rd  cycle that more appear was fluency with score 91.2%.  Besides, for the frequency percentage of students performance from each cycles are more increasing, by the 1st  cycle 55% (enough), the 2nd cycle 70% (good), and the 3rd cycle 85% (very good). Finally, the suggestopedia method in learning speaking English can increase the result of students learning. In fact, the students look like be enthusiastic in learning speaking English. The students were active to joint with this subject from each cycle. By the good atmosphere, conducive situation of the classroom, and soft music made the students to be relax in learning the subject. It also was increase imagination, concentration, and liveliness for the students.